Synthesis and Biological Evaluation of RGD-Cryptophycin Conjugates for Targeted Drug Delivery - Adina Borbély; Eduard Figueras; Ana Martins; Simone Esposito; Giulio Auciello; Edith Monteagudo; Annalise Di Marco; Vincenzo Summa; Paola Cordella; Raffaella Perego; Isabell Kemker; Marcel Frese; et al. (MDPI AG, 2019)
Cryptophycins are potent tubulin polymerization inhibitors with picomolar antiproliferative potency in vitro and activity against multidrug-resistant (MDR) cancer cells. Because of neurotoxic side effects and limited efficacy in vivo, cryptophycin-52 failed as a clinical candidate in cancer treatment. However, this class of compounds has emerged as attractive payloads for tumor-targeting applications. In this study, cryptophycin was conjugated to the cyclopeptide c(RGDfK), targeting integrin αvβ3, across the protease-cleavable Val-Cit linker and two different self-immolative spacers. Plasma metabolic stability studies in vitro showed that our selected payload displays an improved stability compared to the parent compound, while the stability of the conjugates is strongly influenced by the self-immolative moiety. Cathepsin B cleavage assays revealed that modifications in the linker lead to different drug release profiles. Antiproliferative effects of Arg-Gly-Asp (RGD)–cryptophycin conjugates were evaluated on M21 and M21-L human melanoma cell lines. The low nanomolar in vitro activity of the novel conjugates was associated with inferior selectivity for cell lines with different integrin αvβ3 expression levels. To elucidate the drug delivery process, cryptophycin was replaced by an infrared dye and the obtained conjugates were studied by confocal microscopy.